2021
DOI: 10.1093/ve/veab046
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evolution, transmission dynamics, and pathogenicity of avian influenza A (H5N8) viruses emerging in China, 2020

Abstract: Multiple recent outbreaks of highly pathogenic H5N8 viruses originating in aquatic birds frequently occurred in most European countries, Russia, South Korea, and Japan during the winter of 2020–2021, and one zoonotic event of poultry workers infected with novel H5N8 viruses were reported in Russia. Strikingly, these novel H5N8 viruses had emerged and been co-circulating in wild birds and poultry in multiple provinces of China during 2020–2021. In China, the population of aquatic birds has risen significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The viruses from Pakistan are distantly related to A/Astrakhan/3212/2020, responsible for the first human A(H5N8) infection in Russia in late December 2020, clustering in subgroup 8 that contains clade 2.3.4.4b A(H5N8) viruses which circulated in domestic and wild birds across Europe during May 2020-February 2021 (Figure 2c). The mean estimated TMRCA of the HA-H5 virus of subgroup 8 was estimated in early December 2019 (95% HPD: May 2019-March 2020), consistent with previous observation [56]. The H5-HA phylogeny shows that the human strain (A/Astrakhan/3212/2020) is most closely related to two chicken A(H5N8) clade 2.3.4.4b viruses with an estimated TMRCA in late November 2020 (green dotted arrow in Figure 2c, 95% HPD: October 2020-December 2020), indicative of direct transmission from domestic poultry.…”
Section: Molecular Characterizations Of Pakistan A(h5n8) Virusessupporting
confidence: 90%
“…The viruses from Pakistan are distantly related to A/Astrakhan/3212/2020, responsible for the first human A(H5N8) infection in Russia in late December 2020, clustering in subgroup 8 that contains clade 2.3.4.4b A(H5N8) viruses which circulated in domestic and wild birds across Europe during May 2020-February 2021 (Figure 2c). The mean estimated TMRCA of the HA-H5 virus of subgroup 8 was estimated in early December 2019 (95% HPD: May 2019-March 2020), consistent with previous observation [56]. The H5-HA phylogeny shows that the human strain (A/Astrakhan/3212/2020) is most closely related to two chicken A(H5N8) clade 2.3.4.4b viruses with an estimated TMRCA in late November 2020 (green dotted arrow in Figure 2c, 95% HPD: October 2020-December 2020), indicative of direct transmission from domestic poultry.…”
Section: Molecular Characterizations Of Pakistan A(h5n8) Virusessupporting
confidence: 90%
“…In addition, a study on seroprevalence showed that H6 subtype viruses had seropositivity among occupational contact workers in 19 provinces in China [21]. For our part, we recently demonstrated that reassorting human-and bird-origin H5N6 viruses all harbored a segment of H6 origin [22,23]. Altogether, those findings indicated that H6 subtype viruses pose a significant threat to public health.…”
Section: Introductionmentioning
confidence: 61%
“…There remains an important question to answer regarding whether these H5N8 viruses could become the dominant subtype in domestic poultry in China. Our previous study showed that these 2.3.4.4b H5N8 viruses were antigenically distinct from the commercial vaccine strains in China (Zhang et al, 2021). In China, vaccination of chickens can be a major strategy for controlling the spread of AIVs in poultry.…”
Section: Discussionmentioning
confidence: 98%
“…Frequent contact between wild birds and poultry were regarded as the most probable cause of viral introduction into domestic poultry (Zhang et al, 2020a(Zhang et al, , 2021. It is noteworthy that the circulating 2.3.4.4b viruses were antigenically distinct from the clade 2.3.4.4h and 2.3.2.1b vaccine strains in China (Zhang et al, 2021), highlighting the update of H5 subtype vaccine in poultry. The poultry-to-human interface may remain elevated due to possible dissemination of the H5N8 viruses among poultry and wild birds.…”
Section: Introductionmentioning
confidence: 99%